The Challenges and Possibilities of Reducing Deaths from Cryptococcal Meningitis in Sub-Saharan Africa - Farlow, Andrew W. K. (Public Library of Science, 2012)
Andrew Farlow reflects on new research by David Boulware and colleagues, highlighting current challenges in treating cryptoccocal meningitis and the relative neglect of investment in research to treat this disease.